Comparative bioactive properties of Coprinopsis atramentaria extract, organic acids and synthesized derivatives - Heleno, Sandrina A. (2015)
Organic acids, namely phenolic acids, have been largely studied for their bioactivities and, in particular, mushrooms are interesting sources of these compounds [1]. However, very little is known about the bioactive forms in vivo and the mechanisms by which they may contribute towards disease prevention. There is accumulating evidence suggesting that these molecules are rapidly metabolized in the human organism. After absorption from the gastrointestinal tract, phenolic acids suffer conjugation reactions and several changes in their initial structure and circulate in human plasma as conjugated forms, glucuronide, methylated and sulfated derivatives. These changes in their structures may increase or decrease the bioactivity of the initial phenolic acids [2]. In the present work, the extract of Coprinopsis atramentaria, a wild mushroom species from the northeast of Portugal, was studied and revealed interesting bioactive properties (e.g., antioxidant, cytotoxic for human tumor cell fines and antimicrobial), being p-hydroxybenzoic (HA), p-coumaric (CoA) and cinnamic (CA) acids identified in the mentioned extract. Furthermore, methylated and glucuronated derivatives of the mentioned compounds were synthetized and their bioactivities were evaluated and compared with those of the parental molecules and extract. In almost all of the cases the glucuronated and methylated derivatives increased the bioactivities of the parental compounds, revealing stronger properties than the extract, the parental compounds and, in the case of antimicrobial properties, even than the standards used [3]. This report allows the comparison between parental compounds and metabolite derivatives. Therefore, detailed knowledge concerning the conjugative/metabolic events and resulting plasma levels following the ingestion of organic acids-rich diet is crucial for the understanding of their bioactivity.